The thermal stability, structural changeability, and aggregability of glutenin and gliadin proteins induced by wheat bran dietary fiber. Issue 1 (5th December 2018) - Ma, Sen; Han, Wen; Li, Li; Zheng, Xueling; Wang, Xiaoxi
Abstract : Wheat bran dietary fiber (WBDF) has been reported to be responsible for the low quality of whole wheat flour products due to its destructive effect on the gluten matrix. Abstract : Wheat bran dietary fiber (WBDF) has been reported to be responsible for the low quality of whole wheat flour products due to its destructive effect on the gluten matrix. Glutenin and gliadin are the major components of gluten protein and contribute to a proper gluten structure. In this study, the thermostability, surface hydrophobicity, fluorescence characteristics, free sulfhydryl contents, and molecular weight distributions of glutenin- and gliadin-rich fractions were determined after the addition of WBDF. The addition of WBDF to glutenin resulted in an increased surface hydrophobicity and free sulfhydryl content, as well as a red-shift of the fluorescence spectrum. However, the WBDF-modified gliadin fraction changed slightly mainly due to its spherical conformation. Size exclusion chromatography profiles revealed increasing soluble gliadin aggregates and decreasing high molecular weight glutenin fractions as a result of WBDF incorporation. The results from the thermostability analyses exhibited decreased weight loss and decomposition temperatures for both glutenin and gliadin proteins at high WBDF concentration. Our results suggest that changes in the gluten matrix caused by WBDF may largely rely on glutenin structure variation.